“The Triumph of the Ordinary”: Mental Reservation, Racial Profiling and Construction of a Human Social Community in Sherman Alexie’s Ten Little Indians - Shuangshuang Li (Humanities)
In Ten Little Indians, Sherman Alexie presents nine poignant and emotionally resonant stories about Native Americans’ struggle with alienation and stereotypes. Instead of focusing merely on the ethnic identity of American Indians, Alexie writes about a particular group of people sharing similar circumstances and addresses their common humanity, namely their search for love and respect in urban spaces. Alexie questions the authenticity of Indian identity and asserts that a “mental reservation” exists in the minds of Indian people which significantly influences their perceptions of self and community. Race, as a medium of seeing “the other” permeates U.S. society, especially in the wake of terrorist attacks. However, racial profiling has proven to be an ineffective means of detecting criminals and criminal activities, and has obstructed social relationships, bringing emotions of fear, loneliness and grief to urban Indians. In response to the modernity crisis, Alexie explores the American Indian cosmopolitanism in Ten Little Indians, and envisions a human social community based on reciprocity and mutual respect. His concerns regarding ordinary people’s life experiences and their ways of forming healthy relationships exhibit his considerable hope for “the triumph of the ordinary”.